Establishing the reliability and limits of meaningful change of lower limb strength and power measures during seated leg press in elite soccer players - Redden, J.; Stokes, K.; Williams, D. (Journal of Sports Science & Medicine, 2018)
Measurement of lower limb strength, power and asymmetries of soccer players is important for monitoring physical development and injury risk. The aim of the present study was to establish the reliability and limits of meaningful change of single and double leg maximal strength, power and bilateral imbalance measures in elite soccer players using a pneumatic resistance based seated leg press. Thirteen participants undertook an incremental resistance leg press test on three separate testing days within a seven day period. Paired t-tests established no significant differences (p > 0.156) between consecutive tests, whilst `good` reliability (intraclass correlation coefficient-ICC >0.762) and acceptable typical percentage errors (< 6.9%) were observed for maximal resistance, velocity and force pushed as well as average and peak power outputs. Imbalance variables accounting for left and right leg average power output across all repetitions were established as the most reliable imbalance variables, with `good` reliability (ICC > 0.874) and absolute typical error values of 2.1%. Imbalance variables calculated using peak power output or average power output from the last 4 repetitions resulted in weaker reliability (ICC < 0.657) and significant differences between tests, and therefore were considered less suitable for applied use. Subsequently, to better inform the practitioner, limits of meaningful change were calculated for all strength, power and imbalance variables. The current study shows that lower limb strength, and power output variables and average imbalance measures of soccer players assessed through a seated leg press protocol show acceptable levels of reliability, and provides practitioners with limits of meaningful change around parameters to better evaluate test results.